2006
DOI: 10.1007/s11242-006-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Capillary Pressure Function from Resistivity Data

Abstract: A model has been derived theoretically to correlate capillary pressure and resistivity index based on the fractal scaling theory. The model is simple and predicts a power law relationship between capillary pressure and resistivity index (P c = p e · I β ) in a specific range of low water saturation. To verify the model, gas-water capillary pressure and resistivity were measured simultaneously at a room temperature in 14 core samples from two formations in an oil reservoir. The permeability of the core samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Note that the gas slippage is greater in core samples with low permeabilities than in those with high permeabilities. Li and Williams (2006) verified, to some extent, the relationship between capillary pressure and resistivity index (Eq. 8) using the experimental data of gas-water capillary pressure and resistivity measured simultaneously.…”
Section: Validation Of the Relationship Between Relative Permeabilitymentioning
confidence: 72%
See 2 more Smart Citations
“…Note that the gas slippage is greater in core samples with low permeabilities than in those with high permeabilities. Li and Williams (2006) verified, to some extent, the relationship between capillary pressure and resistivity index (Eq. 8) using the experimental data of gas-water capillary pressure and resistivity measured simultaneously.…”
Section: Validation Of the Relationship Between Relative Permeabilitymentioning
confidence: 72%
“…The second approach to determining capillary pressure is the application of the model developed by Li and Williams (2006):…”
Section: Relationship Between Capillary Pressure and Resistivity Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such models have been few. Li and Williams (2006) developed a correlation between resistivity and capillary pressure theoretically; but relative permeability was not considered. Pirson et al (1964) proposed a model to calculate relative permeability from resistivity data; the model reported by Pirson et al (1964) was empirical.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Tyler and Wheatcraft 1990;Li 2009) derived the empirical Brooks-Corey capillary pressure model theoretically from fractal modeling of a porous medium. Recently Li and Williams (2006) and Li (2007Li ( , 2011 developed interrelationship between resistivity index, capillary pressure, and relative permeability using fractal geometry. These studies showed the fractal feature of pore (including fractures) size distribution in different porous media and the capability of fractal geometry as well as its applications in many industries.…”
Section: Introductionmentioning
confidence: 99%